65.6k views
0 votes
Which of the following statements follows from (x - 3)2 = 7? ox2 +9=7 Ox-3=1 / OX-3 = +49 NEXT QUESTION O ASK FOR HELP

User Proppy
by
5.6k points

1 Answer

1 vote

So, given the equation:

We could take the square root to both sides of the equation to obtain that:

So the correct option is B.

Which of the following statements follows from (x - 3)2 = 7? ox2 +9=7 Ox-3=1 / OX-example-1
Which of the following statements follows from (x - 3)2 = 7? ox2 +9=7 Ox-3=1 / OX-example-2
User JuanZe
by
5.4k points